Performance effects of a strength training program in collegiate runners - Younker, A. (Electronic Theses and Dissertations. Paper 3959, 2021)
Research has shown that lower limb asymmetries can negatively impact performance and risk of injury. However, there is little research on the effects of lower limb asymmetry on running performance, nor the effects of strength training on lower limb asymmetry in runners. The purpose of this study was to examine the relationship between jumping ability and asymmetry and long distance running performance, as well as to determine the performance effects a strength training program has on collegiate runners. Data from athlete monitoring of 10 collegiate distance runners and 6 sprinters were analyzed. Athletes (Distance Runners n = 10, Sprinters n = 6) performed static and countermovement jumps at two testing sessions separated by 21 weeks, during which, they participated in a block-periodized strength training program. The athletes were capable of maintaining a minimal amount of kinetic asymmetry during the jump tests and there were no statistically significant correlations between jump height, jump asymmetry, and cross-country race times. After the strength training intervention, the female distance runners significantly improved static jump height (p value = 0.045), countermovement jump height (p value = 0.015), countermovement jump asymmetry percentage (p value = 0.006), and body fat percentage (p value = 0.002). Although there were no other statistically significant changes, there were promising trends in many of the performance variables. These results indicate that there are potential benefits associated with strength training, and coaches should incorporate it into the overall programming for collegiate runners for injury prevention and enhanced performance.